The impact of technological innovation capabilities on competitive advantage and firm performance in the automotive industry in Malaysia - Faridah, Taju Rahim; Yuserrie, Zainuddin (AIP Publishing, 2019)
Technological innovation capabilities (TICs) are important for firms to obtain core competencies and in upgrading a firm’s competitive capabilities. Previous studies rarely examined the relationship between TICs and competitive advantage and firm performance. Moreover, most studies neglect the mediating effect of competitive advantage in the relationship between TICs and firm performance This study uses interviews and the survey method to discuss the relationships governing TIC dimensions (R&D capability, manufacturing capability, networking capability, and human resource capability), competitive advantage, and firm performance. Results are based on empirical data from the automotive industry in Malaysia and are generated by the Partial Least Squares (PLS) method using WarpPLS 6.0. Results show that R&D capability and networking capability improve both competitive advantage and firm performance. However, manufacturing capability only improve firm performance, in contrast with human resource capability only affects competitive advantage. The results of the study also found that competitive advantage significantly impacts on firm performance but does not mediate the effect of TIC dimensions (R&D capability, manufacturing capability, networking capability, and human resources capability) on firm performance. The developed model indicates that automotive industry in Malaysia would perform better with greater emphasis on improving competitive advantage through the enhancement of R&D capability, manufacturing capability, networking capability and human resource capability measured in this study.